2017
DOI: 10.3389/fmicb.2017.01477
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potentials of Lysinibacillus sphaericus ZA9 for Plant Growth Promotion and Biocontrol Activities against Phytopathogenic Fungi

Abstract: There is an ongoing hunt for biologically active compounds that can combat phytopathogenic fungi and improve plant growth without causing any hazards to the environment. Consequently the present study aims at deciphering the plant growth promotion and antifungal capability of Lysinibacillus sphaericus ZA9. The bacterium was previously isolated and identified in our laboratory from maize rhizosphere using 16S rRNA gene sequencing. The test bacterium L. sphaericus ZA9 was found to produce high quantity of IAA (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 43 publications
(52 reference statements)
4
47
1
5
Order By: Relevance
“…e role of PGPB in this nutrient cycling consists of their capacity to synthesize organic acids, so that the consequent soil acidi cation can lead to phosphorus release from mineral phosphate, turning it into soluble and available forms for plants uptake [30,31]. Studies reported L. sphaericus solubilization activity in silicate medium agar and biochar, supporting our results [28,32]. Presumably, L.…”
Section: Treatmentssupporting
confidence: 85%
“…e role of PGPB in this nutrient cycling consists of their capacity to synthesize organic acids, so that the consequent soil acidi cation can lead to phosphorus release from mineral phosphate, turning it into soluble and available forms for plants uptake [30,31]. Studies reported L. sphaericus solubilization activity in silicate medium agar and biochar, supporting our results [28,32]. Presumably, L.…”
Section: Treatmentssupporting
confidence: 85%
“…(especially the HAQs), and a routine silica column chromatography was failed to purify them. Although, Naureen et al (2017) have successfully purified the secondary metabolites (2-pentyl-4-quinolinecarboxylic acid and 1- methylcyclohexene) from Lysinibacillus sphaericus ZA9 but the chemistry of these metabolites is significantly different from the HAQs identified in the present study. A high-quality preparatory HPLC system may be required to purify various analogs of HAQs (Wang et al, 2011).…”
Section: Discussioncontrasting
confidence: 63%
“…In addition, A. terreus produces glucanase enzyme and mevastatin, the activities of which are suggested to play a role in the antagonism against P. aphanidermatum . In addition to the active role of enzymes in biological control, several other secondary metabolites contribute effectively to the control of plant pathogens such as siderophore (Schwyn and Neilands, 1987; Naureen et al, 2017) and Hydrogen cyanide (HCN) (Ramette et al, 2003). Baakza et al (2004) indicated production of siderophore by Aspergillus species including A. terreus .…”
Section: Discussionmentioning
confidence: 99%